Incorporation With Verbal Deletion In Mandailing Language - Nursaima Harahap; Mulyadi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Incorporation in the Mandailing language occurs due to changes of verb position which results in deletion of verb. The theory used to analyze this incorporation of verb deletion is one presented by Fillmore (1988) referring to Jehane’s. Meanwhile, the method used in this study is based on Labov’s. According to Labov, the data of linguistic research are obtained from text, elicitation, intuition, experiment, and observation. Von Humboldt states that the term incorporation is the unification of lexical morphemes and words. The result of this analysis indicates that the incorporation in Mandailing occurs typologically rather than polysynthetically. The forms or types of incorporation in this language are apparently quite broad, varied, and applied clearly without changing the meaning of each incorporation. One of the incorporation forms or types results in incorporation with verb deletion. The kinds of incorporation with verb deletion based on the cases are objective, instrumental, locative, translative, and state incorporations. The incorporation process of verb deletion happens because the incorporating case changes its function. The case is verbalized by verb affix, and then the incorporation process causes changes in syntactic valence and construction.